Membangun Kekebalan Tubuh: Pengetahuan tentang Peran Prebiotik dan Probiotik dalam Kesehatan Anak: Crafting Paediatric Immunity: The Science of Prebiotic, Probiotic, and Synbiotic Roles in Child Health - Sutanto, Luciana Budiati; Dilantika, Charisma; Pratiwi, Dessy; Latarissa, Irma Rahayu (Universitas Airlangga, 2025)
Background: The gut microbiota affects Children's immune system, which interacts with the immune system to support a healthy body. Prebiotics and probiotics, alongside their combination in the form of synbiotics, have demonstrated significant potential for enhancing immune health in children. Objectives: This article aims to review the role of prebiotics, probiotics, and synbiotics in supporting pediatric immune health by discusses their mechanisms of action, clinical evidence of benefits, and their impact on infection risk reduction, gut health enhancement, and improved vaccine effectiveness. Methods: A comprehensive literature review was conducted by utilizing recent studies and clinical trials on the effects of prebiotics, probiotics, and synbiotics on paediatric immune health. Discussions: Prebiotics, probiotics, and synbiotics play a crucial role in supporting paediatric immune health by optimizing gut microbiota balance and facilitating the production of beneficial metabolites, such as short-chain fatty acids (SCFAs), which subsequently strengthen gut barrier function and modulate immune responses. Prebiotics provide essential nutrients for beneficial bacteria, probiotics directly interact with immune cells, and synbiotics synergistically combine these benefits, demonstrating effectiveness in reducing infections, enhancing vaccine responses, and preventing allergies. Clinical studies highlight their potential to improve gastrointestinal health, reduce inflammation, and strengthen immunity, emphasizing their importance as safe and effective interventions for children's health. Conclusions: Prebiotics, probiotics, and synbiotics demonstrate significant potential in supporting children's immune health through mechanisms that improve gut microbiota balance and enhance immune function. Despite encouraging findings, additional research is essential to determine optimal dosages, long-term safety, and individualized strategies for their clinical application.